2007
DOI: 10.5194/aab-50-388-2007
|View full text |Cite
|
Sign up to set email alerts
|

Foot pad health, plumage condition, integument and claw length of Lohmann Silver laying hens kept in small aviary housing systems, furnished cages and an aviary housing system

Abstract: In the 3rd, 6th, 9th and 12th laying month, foot pad health, plumage condition, integument and claw length were evaluated in 432 Lohmann Silver laying hens kept in three different housing systems: a small aviary housing system (Eurovent 625a-EU, EV) with different perch levels, a furnished cage system (Aviplus, AP) and an aviary (Voliere Natura, AV). Foot health was scored for hyperkeratosis and lesions on a scale from 1 (normal) to 5 or 4 (severe). Plumage condition was assessed with scores from 1 (worst) to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…Perches and other equipment can lead to problems in plumage condition in laying hens (Sepeur et al, 2015). Significant deterioration of plumage was found with increasing age of hens, which is in accordance with the results of other authors (Rönchen et al, 2007;Distl, 2013, Schreiter et al, 2020).…”
Section: Resultssupporting
confidence: 90%
“…Perches and other equipment can lead to problems in plumage condition in laying hens (Sepeur et al, 2015). Significant deterioration of plumage was found with increasing age of hens, which is in accordance with the results of other authors (Rönchen et al, 2007;Distl, 2013, Schreiter et al, 2020).…”
Section: Resultssupporting
confidence: 90%
“…In addition, foot pad health may be influenced by the provision of perches. Although Appleby et al (1992) reported a positive effect of perches on layers' foot pad condition, many authors found a higher incidence of foot pad problems in hens housed with perches Glatz and Barnett, 1996;Rönchen et al, 2007).…”
Section: Introductionmentioning
confidence: 93%
“…Wet litter, a high level of ammonia, and poorly designed and maintained perches have been associated with foot injuries in litter systems (19,24,25). In cage systems, hens are kept on wire mesh, which may cause superficial epithelial lesions and hyperkeratosis (26,27). In this study the occurrence of foot injuries was low and almost no severe inflammation (i.e., bumblefoot) was seen in any system.…”
Section: Discussionmentioning
confidence: 56%